Association between psychological resilience and global health status/quality of life in patients with brain metastases after resection of primary non-small cell lung cancer - Caijun Dong; Yafen Jiang (Frontiers in Psychiatry, 2026)
Background Brain metastases after resection of primary non-small cell lung cancer (NSCLC) impose substantial burdens. We examined the concurrent association between psychological resilience and global health status/quality of life (GHS/QoL). Methods This single-center retrospective study included 207 adults who first developed brain metastases after primary NSCLC resection. Records from the 25-item Connor-Davidson Resilience Scale (CD-RISC), European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30), and European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Brain Neoplasm Module 20 (EORTC QLQ-BN20), collected at the same clinically stable outpatient assessment 4–12 weeks after brain-metastasis diagnosis, were linked to retrospectively extracted clinical data. Pearson correlations and a prespecified full-covariate multivariable linear regression model were used. Results CD-RISC scores correlated positively with all QLQ-C30 functioning scales and GHS/QoL and negatively with the three QLQ-C30 symptom scales and four QLQ-BN20 multi-item symptom scales (all Benjamini–Hochberg-adjusted q < 0.001). Each 1-point increase in CD-RISC total score was associated with a 0.452-point higher adjusted GHS/QoL score (95% confidence interval, 0.326–0.578; P < 0.001). Higher Karnofsky Performance Status and college-level education were associated with higher GHS/QoL, whereas pretreatment clinical tumor-node-metastasis stage IIIB or IVA, ≥4 brain metastases, and 30-day complications after lung resection were associated with lower GHS/QoL. Conclusions Greater psychological resilience was concurrently associated with better GHS/QoL and lower QLQ-BN20 multi-item symptom scores. These findings support integrated assessment of resilience, function, and symptoms; temporal direction requires longitudinal confirmation, and intervention effects require prospective trials.